Morphological and Syntactic Behaviour of Lubukusu Locative Clitics among Native Speakers of Bungoma County, Kenya - Nyongesa Sharon Nelly; David Wafula Lwangale (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study examined how Lubukusu, a Bantu dialect of Luluhyia language in Bungoma County has locative clitics and their impact in communication. The study aimed at establishing the effects of Lubukusu locative clitics in communication among the native speakers of Lubukusu in Bungoma County by looking at the morphological and syntactic behavior of Lubukusu clitics. This study employed the Stratal Optimality Theory by Anderson (2005) where he describes the phonological behavior of clitics. This study relied on the pre-existing data and adopted a qualitative research approach by use of descriptive research design. The target populations were the native speakers of Lubukusu from Bungoma County. The study employed simple random sampling and probability sampling techniques so that each respondent had an equal chance of being selected fairly. The study used qualitative data collection methods by use of interview schedule. Interview schedule were used because the researcher did not want to limit the respondents on the use of Lubukusu locative clitics. The qualitative data were analyzed by descriptive and content analysis to get information. The researcher ensured that while carrying out this study, the confidentiality of the respondents was adhered to. The study found out that Lubukusu locative clitics had morphological properties that were reconciled with their syntactic properties and phonological properties in order to aid in communication within a sentence structure. These findings implied that Lubukusu locative clitics have properties that were peculiar and that can be interpreted by assuming that they become part of the adjacent words at the phonological level but they are independent elements at the syntactic level of analysis. That is why they both were and were not words.